Aspects of Standardization in the Juice of the Herbs Alchemilla vulgaris - E. V. Cheremnykh; E. V. Zorina; V. D. Belonogova (Разработка и регистрация лекарственных средств)
Introduction. The features of the chemical composition and the identified pharmacological activities of substances from fresh raw materials of the Alchemilla vulgaris allow us to predict the prospects for the use of juice from the herb Alchemilla vulgaris in medical practice. The creation of drugs based on juices from fresh herb Alchemilla involves the development of methods for their standardization.Aim. To determine the methods of qualitative analysis for the identification and quantitative assessment of the main group of biologically active substances in Alchemilla vulgaris juice.Materials and methods. The herb Alchemilla vulgaris for juice production was harvested during the flowering period in various habitats. The qualitative composition of the phenolic compounds of the juice was studied by paper chromatography and thin layer chromatography (TLC). The quantitative determination procedure was developed and validated on an SF-2000 spectrophotometer.Results and discussion. Paper chromatography (CP) in the juice revealed derivatives of cinnamic and phenolcarboxylic acids, a group of flavonoids with a predominance of flavones and flavonols, rutin was identified among the dominant ones. The TLC in the butanol : acetic acid : water system (4 : 1 : 2), we achieved optimal separation of substances and identified rutin, which was proposed as the main substance in juice standardization. Correspondence of the configuration of the differential spectrum of the complex of cuff juice flavonoids with aluminum chloride to the spectrum of a similar complex of rutin SS and the results of TLC give grounds to use rutin as a standard. The best option when choosing an aliquot for quantitative determination of reliable results showed the use of 0.2 ml of juice. The content of flavonoids in the studied juice samples ranged from 2.15 ± 0.24 % to 7.34 ± 0.16 %.Conclusion. TLC in the butanol-acetic acid-water system (4 : 1 : 2) can be used to authenticate the juice from the herb Alchemilla vulgaris. The parameters of the method of quantitative determination are developed taking into account the variation in the ratio of the water component and the dry residue in the juice. The method is valid and can be used to standardize juice from the herb Alchemilla vulgaris. The taxation of Alchemilla vulgaris juice samples showed the variability of the content of flavonoids in the juice depending on the growing conditions.